A Novel Approach to Addressing Surgical Resource Scarcity in Low-Income Countries - Gasoma, Elmuhtadibillah Babiker Yousif; Marouf, Mohamed Ahmed; Elhag, Mohammed; Shammed, Hady; Siddig, Ikhlas Abdalla (The Surgery Journal, 2025)
Resource scarcity is a persistent challenge in low-income countries, significantly impacting surgical outcomes. Traditional solutions often fail to address the root causes, leading to poor patient outcomes. This study presents a novel, context-driven approach to optimize the use of limited surgical resources in rural Sudan.A multidisciplinary team conducted a comprehensive needs assessment at a rural hospital in Sudan, identifying critical gaps in surgical capacity. Based on these findings, we implemented a multifaceted intervention that included the local production of surgical supplies, the introduction of mobile surgical teams, and the utilization of telemedicine for remote consultations. Data were collected over 12 months to evaluate the impact on surgical outcomes, resource utilization, and patient satisfaction.The intervention led to a 35% increase in the number of surgeries performed, with a significant reduction in operative delays. The local production of surgical supplies reduced dependency on external suppliers, lowering costs by 25%. The introduction of mobile surgical teams decreased patient referral rates to distant hospitals by 40%. Telemedicine consultations provided crucial specialist input in 80% of complex cases, resulting in improved decision-making and patient care.This study demonstrates that a locally tailored, resource-sensitive approach can significantly enhance surgical capacity and outcomes in low-income settings. The success of this intervention suggests its potential scalability to other resource-limited regions, offering a sustainable solution to the challenges of surgical care in a changing world.
Keywords: global surgery; surgical challenges; low-income countries; mobile surgical teams; telemedicine